2012
DOI: 10.1002/ejsp.872
|View full text |Cite
|
Sign up to set email alerts
|

Punishing and compensating others at your own expense: The role of empathic concern on reactions to distributive injustice

Abstract: When confronted with violations of justice, people may be motivated not only to punish the violator, but also to compensate the victim. Whereas prior research has primarily concentrated on the question of when people are willing to punish, we provide a more comprehensive picture by also studying the willingness to compensate and by assessing the moderating role of empathic concern. Study 1 introduces the altruistic compensation game and shows that especially high empathic (compared to low empathic) people are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
174
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(196 citation statements)
references
References 18 publications
17
174
3
2
Order By: Relevance
“…We further expect compensation to be a direct result of the anger, which is independent from the empathic concerns that may be triggered simultaneously (Leliveld et al 2012). Some initial support for this expectation can already be found in the experiment by Lotz et al (2011b), who found that visibility mattered for empathy: the goal of empathy is to comfort someone, but if the victim does not know about the unfair allocation there is no one to comfort.…”
Section: First-party and Third-party Angermentioning
confidence: 76%
See 4 more Smart Citations
“…We further expect compensation to be a direct result of the anger, which is independent from the empathic concerns that may be triggered simultaneously (Leliveld et al 2012). Some initial support for this expectation can already be found in the experiment by Lotz et al (2011b), who found that visibility mattered for empathy: the goal of empathy is to comfort someone, but if the victim does not know about the unfair allocation there is no one to comfort.…”
Section: First-party and Third-party Angermentioning
confidence: 76%
“…Finally, studies that did include positive consequences typically did not directly measure situational, state anger. For example, Leliveld et al (2012) and Prooijen (2010) looked at prosocial consequences after injustice but did not include a measurement of anger. Deffenbacher et al (1996) showed a positive correlation between trait anger and aggressive consequences, and Vitaglione and Barnett (2003) showed that there was no direct relation between trait empathic anger and helping or punishing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations